EFFECT OF TASK BASED INSTRUCTION ON ENGLISH SPEAKING SKILLS AT ELEMENTARY SCHOOL LEVEL - Shahid Raza; Sajida Ghani; Dr. Sumaira Kulsoom; Dr. Muhammad Naeem Sarwar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Teaching English speaking skill is considered more difficult than teaching any other language skill. It has been found that despite receiving good scores, students' speaking proficiency in the English language is not very good. This is also due to our syllabi, assessment system and traditional teaching methods. The objective of the current study was to find out the effect of Task Based Instruction (TBI) on the English-speaking skills of eighth-class students. Matching only pre-test posttest group design was used. Experimental group was selected randomly. Speaking test developed by the researchers was used for the collection of data. Independent sample t-test and repeated measures paired sample t-test were used to find the mean difference between two groups. Data analysis showed that the TBI significantly improved the speaking skills of the experimental group. In the end suggestions for future researches have also been provided.